2021
DOI: 10.1038/s41586-021-04058-1
|View full text |Cite
|
Sign up to set email alerts
|

Transposon-associated TnpB is a programmable RNA-guided DNA endonuclease

Abstract: Transposition has a key role in reshaping genomes of all living organisms1. Insertion sequences of IS200/IS605 and IS607 families2 are among the simplest mobile genetic elements and contain only the genes that are required for their transposition and its regulation. These elements encode tnpA transposase, which is essential for mobilization, and often carry an accessory tnpB gene, which is dispensable for transposition. Although the role of TnpA in transposon mobilization of IS200/IS605 is well documented, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
241
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(250 citation statements)
references
References 46 publications
8
241
0
1
Order By: Relevance
“…Similarly to Cas9 and Cas12, the nucleases of IS200/IS605-like transposons form a complex with a distinct guide RNA encoded within the same transposon ( Altae-Tran et al, 2021 ). However, in these elements, the guide RNAs are not responsible for cleaving foreign DNA, but rather might direct the transposons to specific integration sites in the host chromosomal DNA; the details of the functions of these nucleases in transposons remain to be studied ( Altae-Tran et al, 2021 ; Karvelis et al, 2021 ). Collectively, these observations indicate that most if not all major components of CRISPR-Cas systems originated via exaptation of MGE genes.…”
Section: Mainmentioning
confidence: 99%
“…Similarly to Cas9 and Cas12, the nucleases of IS200/IS605-like transposons form a complex with a distinct guide RNA encoded within the same transposon ( Altae-Tran et al, 2021 ). However, in these elements, the guide RNAs are not responsible for cleaving foreign DNA, but rather might direct the transposons to specific integration sites in the host chromosomal DNA; the details of the functions of these nucleases in transposons remain to be studied ( Altae-Tran et al, 2021 ; Karvelis et al, 2021 ). Collectively, these observations indicate that most if not all major components of CRISPR-Cas systems originated via exaptation of MGE genes.…”
Section: Mainmentioning
confidence: 99%
“…While successful functional innovations by co-option of these systems may be unlikely, the very frequent transfer of systems and their rapid evolution may result in such a high rate of novel combinations of domains that some will eventually evolve to become novel defense systems. Such processes of co-option may have been at the independent origins of both Cas-9 and Cas-12 proteins from transposon-encoded RNA-guided endonucleases [ 75 , 76 ].…”
Section: Introduction: Mobile Genetic Elements Drive Gene Flow At a (Sometimes Hefty) Costmentioning
confidence: 99%
“…The role of IscB and TnpB in the transposon life cycle remains unknown. Recently, however, it has been shown that these proteins are RNA-guided nucleases that utilize a small RNA encoded by an adjacent gene (denoted ωRNA, after Obligate Mobile Element Guided Activity, OMEGA) to target specific sequences in a manner resembling the CRISPR mechanism [ 49 , 50 ]. All these proteins contain homologous RuvC-like nuclease domains, but, likely, specific evolutionary relationships can be traced.…”
Section: Introductionmentioning
confidence: 99%